Trends of consumption and purchase intention towards organic food / Aishah Musa and Nor Azirah Ahmad - Musa, Aishah; Ahmad, Nor Azirah (2017)
This undergraduate project is to find out the trend of organic food among Malaysian. Generally, the demand of organic food is increasing rapidly due to the awareness on the benefits of organic food. The production of organic food must follow the established organic standard and each organic food must be certified by certifying body. Based on other research, synthetic fertilizers, pesticides, genetically modified organisms (GMOs), food additives, and sewage sludge are not allowed in the production of organic food. Consumer can purchase organic food at supermarkets, organic food stores, and farmers market. In Malaysia, the local organic food industry is still small as compared to other countries, but more than 60% of organic food products are imported to Malaysia. Gender is often seen as the strongest association with organic food consumption and knowledge. However, nowadays the acceptance of organic food among young people is high. In addition, to have consistent supply due to growth of demand on organic food, various programs and activities have been conducted by Malaysian Agricultural Research and Development Institute on the organic farming sector. Therefore, the purpose of this study is to critically discuss the three significant factors of purchase intention towards organic food among Malaysian, which include environmental concern, organic knowledge and education, and health concern. According to previous research, the factors of Malaysian purchasing organic food are those three factors. Furthermore, through the argumentative research design it can increase the purchase intention towards organic food among Malaysian.